Unlocking value out of India's rainfed farming areas. - Sharma, Bharat R. (International Water Management Institute, 2012)
Low and uncertain crop yields and concentrated poverty in the vast rainfed regions, diminishing returns from the public irrigation systems, climate change induced chaotic fluctuations in the hydrologic regimes and a large demand-supply gap in non-cereal food items are all compelling reasons for the need to realise the production potential of rainfed farming areas. Little control over the rainfall and absence of suitable mechanisms for storing or conserving surplus rain to meet the critical water needs is the major cause for low yields and high distress in rainfed regions. The dominant rainfed districts covering 27.5 million ha of rainfed farms and contributing about 85 percent of the rainfed production in India, also generate 114 billion cubic metre (BCM) of harvestable surplus rainfall. A small fraction of this water when harvested in suitable structures and applied as life-saving supplementary irrigation shall produce average increase of 50 percent in total production, besides setting into motion several other multiplier effects. The proposal is economically viable at national level especially for rainfed rice, pulses and oilseeds. This discourse also needs to include the rainfed regions of the East and North East though with a different program matrix. Recent success stories in Gujarat, Madhya Pradesh and West Bengal are testimony to the potential of enhanced productivity under rainfed farming. A new paradigm comprising flexible strategies for selection of the interventions; setting up of Innovation Platforms for wider stakeholder participation, communication and decision making; and integration of echnologies, institutions and policies has been suggested for successful implementation of the proposed plan to unlock the value out of rainfed farming areas of India and elsewhere.